Curcumin Mitigates TNFα‐Induced Caco‐2 Cell Monolayer Permeabilization Through Modulation of NF‐κB, ERK1/2, and JNK Pathways. Issue 21 (3rd March 2022) - Iglesias, Dario E.; Cremonini, Eleonora; Oteiza, Patricia I.; Fraga, Cesar G.
Abstract : Scope: This work studies the capacity of curcumin to inhibit tumor necrosis alpha (TNFα)‐induced inflammation, oxidative stress, and loss of intestinal barrier integrity, characterizing the underlying mechanisms. Methods and Results: Caco‐2 cell monolayers are incubated with TNFα (10 ng mL –1 ), in the absence or presence of curcumin. TNFα causes an increase in interleukin (IL)‐6 and IL‐8 release, which is inhibited by curcumin in a dose‐dependent manner (half‐maximal inhibitory concentration (IC50 ) = 3.4 µM for IL‐6). Moreover, TNFα leads to: i) increased intercellular adhesion molecule 1 (ICAM‐1) and NLRP3 inflammasome expression; ii) increased cell monolayer permeability and decreased levels of tight junction proteins; iii) increased cellular and mitochondrial oxidant production; iv) decreased mitochondrial membrane potential and complex I‐III activity; v) activation of redox‐sensitive pathways, i.e., nuclear factor‐kappa B (NF‐κB), extracellular signal‐regulated kinase 1/2 (ERK1/2), and c‐Jun N‐terminal kinases (JNK); and vi) increased myosin light‐chain kinase (MLCK) expression and phosphorylation levels of myosin light‐chain protein MLC. Curcumin (2–8 µM) inhibits all these TNFα‐triggered undesirable outcomes, mostly showing dose‐dependent effects. Conclusion: The inhibition of NF‐κB, ERK1/2, and JNK activation could be in part involved in the capacity of curcumin to mitigate intestinal inflammation, oxidant production, activation of redox‐sensitive pathways, and prevention of monolayer permeabilization. These results support an action of dietary curcumin in sustaining gastrointestinal tract physiology. Abstract : Curcumin mitigates TNFα‐mediated inflammation, barrier permeabilization, and increased oxidants production in Caco‐2 cell monolayers. Curcumin mainly acts modulating redox‐sensitive pathways.